INDIVIDUAL DIFFERENCES AND STRESS-PERFORMANCE RELATIONSHIP - Kazmi, Rubina; Amjad, Shehla; Khan, Dilawar (Journal of Ayub Medical College Abbottabad, 2009)
Background: Medicine is a high risk profession. Infectious diseases, dealing with difficult patients, accidents on the job, and other hazards have shortened the careers of many practitioners. The extent to which they experience stress turns into poor performance in terms of quality of patient care. Personality traits are often thought to affect the stress that a person perceives. Specific types of personalities seem to be more susceptible to the effects of stress than others. Job performance is associated with different levels of stress. The purpose of the present study was to investigate any effect of job stress on job performance and effect of personality type on the stress-performance relationship. Methods: All 55 house officers enrolled at Ayub Teaching Hospital at the time of study were included in the study. Primary data was gathered through questionnaire designed to address personality type and to gathered information about job stress and performance. Individual semi-structured interviews and observations were used to collect information in order to find out how the work patterns have been influenced by environmental factors. The data obtained through questionnaire was analysed using the statistical methods including descriptive statistics, Spearman’s correlation and multiple regression. Results: The results indicated that Type A individuals tend to experience more stress than Type B, however no major statistical differences were found. Type A individuals performed slightly better than Type B. Conclusion: Identification of house officers’ personality traits will be helpful in assessing stress and designing different stress coping strategies to reduce their level of stress and improve their performance. The correlation between job stress and job performance among house officers with Type A personality characteristics is high. Keywords: Job stress, Occupational stress, Personality Type, Performance